Modified Atomic Orbital Calculations of Energy and Width of the 2pns 1P\(^°\) and 2pnd1P\(^°\) Rydbergs Series of Be-like N\(^3+\), O\(^4+\), F\(^5+\) and Ne\(^6+\) Ions - Diallo, A.; Ba, M. D.; Badiane, J. K.; Gning, M. T.; Sow, M.; Sakho, I. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
We report accurate energy resonances and natural widths belonging to the 1s\(^2 \)2s\(^2\) \(^1\)S\(_0 →\) (2pnl) \(^1\)P\(^°\) and 1s\(^2 \)2s 2p \(^3\)P\(_0 →\) 1s\(^2\)2p [\(^2\)P\(^°\)] np \(^3\)P transitions in the Photoionization spectra of the Be-like N\(^3+\), O\(^4+\), F\(^5+\) and Ne\(^6+\) ions. Calculations are performed in the framework of the Modified Orbital Atomic Theory (MAOT). Excellent agreements are obtained with available experimental and theoretical literature data. The present calculations provide benchmark data for the diagnostic and for the modeling of astrophysical and laboratory plasmas.